Air traffic control : observations on FAA's modernization program : statement of Gerald L. Dillingham, Associate Director, Transportation Issues, Resources, Community, and Economic Development Division, before the Subcommittee on Aviation, Committee on Commerce, Science, and Transportation, U.S. Senate - Dillingham, Gerald Lee, 1947- (Washington, D.C. : The Office ; Gaithersburg, MD (P.O. Box 6015, Gaithersburg 20884-6015) : The Office [distributor], [1998], 1998)
26 pages ; 28 cm
Cover title.;"February 26, 1998.";Includes bibliographical references.;Microfiche. [Washington, D.C.] : U.S. General Accounting Office, [1999?] 1 microfiche : negative.